Underwater wild : my octopus teacher's extraordinary world - Foster, Craig (Filmmaker); Frylinck, Ross (Houghton Mifflin Harcourt, 2021)
"From the creators of the hit documentary My Octopus Teacher, an immersive journey into the underwater world that inspired it--and holds transformative lessons for us all. Craig Foster and Ross Frylinck regularly dive together in the awe-inspiring kelp forests off South Africa, without wetsuits or oxygen tanks. Craig had dived this way for years, including alongside the octopus that inspired My Octopus Teacher. In Ross, he found a kindred spirit, someone who also embraced the ancient methods of acclimating his body to frigid waters, but whose eyes had not yet adjusted to the transcendent wonder Craig saw each time they dove. In the heart-wrenching stories that make up this unforgettable book, we swim alongside Ross as he grows from skeptic to student of the underwater wild. And in the revelatory marine science behind the stunning photos, we learn how to track sea hares, cuttlefish, and limpets, and we witness strange new behaviors never before documented in marine biology. We realize that a whole world of wonder, and an innate wildness within us all, emerge anew when we simply observe. My Octopus Teacher has captivated millions who long to connect with the natural world. Now, with Underwater Wild, the divers behind the film reveal a new vision of the sea, one full of wonder, new insights into marine biology, and life-changing teachings for even the most land-bound of us"--